2016
DOI: 10.25159/2520-5293/1485
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Nurses Towards Patient Care at a Rural District Hospital in the Kwazulunatal Province of South Africa

Abstract: It is important for nurses to have positive attitudes towards patient care if good quality care is to be provided. This study explored nurses’ attitudes towards providing care to patients in one rural district hospital in KwaZulu-Natal from the perspective of the nurses themselves, and from the patients’ perspective. We conducted an explorative qualitative study. Thirteen focus group discussions were conducted with professional/enrolled nurses, enrolled nurse assistants and patients. Discussions were audio-rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…They verbally abuse patients, and in some cases, they neglected patients by withholding care. 29 In support, the NDoH, the Minister of Health, has identified the staff’s attitude as a key health system challenge in the country and has therefore included it in the six ministerial priority areas for patient-centred care in striving towards the goal to achieve rendering of quality health care services. 9…”
Section: Discussionmentioning
confidence: 99%
“…They verbally abuse patients, and in some cases, they neglected patients by withholding care. 29 In support, the NDoH, the Minister of Health, has identified the staff’s attitude as a key health system challenge in the country and has therefore included it in the six ministerial priority areas for patient-centred care in striving towards the goal to achieve rendering of quality health care services. 9…”
Section: Discussionmentioning
confidence: 99%
“…Research confirms that South African hospitals and clinics are reported to experience these negative incidents. 32 Previous studies illustrate ‘attitude’ in a person’s tone of voice but which is often communicated loudly and clearly through non-verbal communication. Considering a negative or a poor attitude conjures up a picture of a person who looks miserable.…”
Section: Discussionmentioning
confidence: 99%
“…That is, there is a need for greater involvement of patients in the decision-making process and that they are given adequate information to make informed decisions in collaboration with their healthcare providers and thus be more empowered in the management of their illness. This would reduce the patriarchal nature of healthcare delivery which characterizes the African context and especially the Ghanaian healthcare delivery system (Haskins, Phakathi, Grant, & Horwood, 2014). This implies that shared decision making is the very foundation of patient-centred care.…”
Section: Discussionmentioning
confidence: 99%